PERSEPSI MAHASISWA DAN TUTOR TENTANG KEJADIAN KRITIS SELAMA DISKUSI TUTORIAL DAN JENIS-JENIS INTERVENSI TUTOR TERHADAP KEJADIAN TERSEBUT - , AMELIA DWI FITRI; , Prof dr. Harsono, Sp.S (K), ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Backgorund. Tutorial group discussion is one of the key features of PBL. The tutorfacilitated group discussion is not always work as planned. Critical incidents during tutorial is one of the factors that may hinder group dynamics. Six factors hindering group dynamics (unequal participation, lack of cohesion, lack of motivation, lack of elaboration, lack of interaction, and personality problem), play role in critical incidents during tutorial. Tutorâs and studentsâ perception on critical incidents are affected by each individual point of view on an incident. The point of view will influence intervention expected by students and actual intervention done by tutor. Tutorâs capability to intervent accordingly is one of the factors needed to ensure group discussion to progress well. Objective. The aim of this research is to identify students and tutors perception on critical incindents during tutorial and types of of intervention done by tutor to overcome these incidents. . Method. This is a mixed-method research which combines quantitative and qualitative approaches. 352 students of 4 batches and 21 tutors involved in this research. Studentsâ and tutorsâ perception on critical incidents were collected using questionnaire consist of 36 Likert-scale items, and 2 open-ended questions. Interventions done by tutors was further explored using focus group discussion with tutor and students, based on quantitative result. Result. Similar perception was found in both students and tutors regarding the factor influenced critical incidents during tutorial the most, which was unequal participation. Nevertheless, different perception was found between students and tutors on factor that hindered discussion which require tutor intervention